Confocal images of circulating tumor cells obtained using a methodology and technology that removes normal cells - Balasubramanian, Priya (2009)
A completely negative enrichment technology was used to detect circulating tumor cells, CTCs, in the peripheral blood of head and neck cancer patients. Of 32 blood samples, 63 percent contained CTCs and the number of CTCs identified per ml of blood collected ranged from 0 to 214. The final purity ranged from 1 CTC in 9 total cells to 1 CTC in 20,000 total cells, the final purity being both a function of the number of CTCs and the performance of the specific enrichment. Consistent with previous reports, CTC were positively identified if: 1) they contained a nucleus based on DAPI stain, 2) stained positive for cytokeratins, and 3) have a high nuclei to cytoplasmic ratio. In addition, for a blood sample to be considered positive for CTCs, the enriched sample must be positive for Epithelial Growth Factor Receptor, EGFR, as measured by RT-PCR. While most of the blood samples were obtained during surgery, a number were taken prior to, and during surgery. In all of the pre- and post- surgery paired samples, significant numbers of CTCs were detected. A number of these enriched samples were observed under confocal microscope in addition to the microscopic observations under traditional wide-field fluorescent microscope. As expected, the FITC stained cytokeratins appeared in the cytoplasm and the average size of these positively stained cells, on the cytospin, was in the range of 8-12 microns. Future studies will involve the investigation if cancer stem cell and mesenchymal markers are present on these CTCs and correlations of patient outcome to the number and type of CTC present.